2018
DOI: 10.5812/ijpbs.13091
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Resilience and Stress Coping Styles on Suicide Attempts in Females Reporting Spouse-Related Abuse

Abstract: Background: Spouse-related abuse involves a wide range of behaviors by the partner and has many debilitating consequences for the victim, such as suicide attempt. Objectives: The aim of this study was to predict the effect of resilience and stress coping styles on the likelihood of suicide attempt in females reporting spouse-related abuse. Methods: The present descriptive comparative study was conducted on 150 female victims of spouse-related abuse in the city of Ilam, Iran, during year 2016. They were matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 26 publications
(32 reference statements)
1
15
0
Order By: Relevance
“…Asadi et al, 2019; Z. S. Asadi et al, 2013; Asian et al, 2019; Barkho et al, 2011; Basar & Demirci, 2018; Daoud et al, 2017; Diop-Sidibé et al, 2006; Eldoseri et al, 2014; Elnashar et al, 2007; Ergin et al, 2005; Fageeh, 2014; Falb et al, 2019; Faramarzi et al, 2005; Ghahhari et al, 2008; Gibbs et al, 2018; Habib et al, 2011; Haj-Yahia & Clark, 2013; Hajian et al, 2014, 2018; Hamdan-Mansour et al, 2011; Jamali & Javadpour, 2016; Kaplan et al, 2011; Khayat et al, 2017; Mayda & Akkuş, 2004; Metheny & Stephenson, 2019; Moghaddam Hosseini et al, 2013; Mohammadbeigi et al, 2019; Mohammadkhani et al, 2009; Nouri et al, 2012; Oyekcin et al, 2012; Poornowrooz et al, 2019; Rahmatian & Hosseini, 2015; Ramiro et al, 2004; Saffari et al, 2017; Seedhom, 2012; Sen & Bolsoy, 2017; Tashkandi & Rasheed, 2010; Tokuç et al, 2010; Vakili et al, 2010; Vaseai et al, 2019; Vyas, 2017; Yount & Li, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Asadi et al, 2019; Z. S. Asadi et al, 2013; Asian et al, 2019; Barkho et al, 2011; Basar & Demirci, 2018; Daoud et al, 2017; Diop-Sidibé et al, 2006; Eldoseri et al, 2014; Elnashar et al, 2007; Ergin et al, 2005; Fageeh, 2014; Falb et al, 2019; Faramarzi et al, 2005; Ghahhari et al, 2008; Gibbs et al, 2018; Habib et al, 2011; Haj-Yahia & Clark, 2013; Hajian et al, 2014, 2018; Hamdan-Mansour et al, 2011; Jamali & Javadpour, 2016; Kaplan et al, 2011; Khayat et al, 2017; Mayda & Akkuş, 2004; Metheny & Stephenson, 2019; Moghaddam Hosseini et al, 2013; Mohammadbeigi et al, 2019; Mohammadkhani et al, 2009; Nouri et al, 2012; Oyekcin et al, 2012; Poornowrooz et al, 2019; Rahmatian & Hosseini, 2015; Ramiro et al, 2004; Saffari et al, 2017; Seedhom, 2012; Sen & Bolsoy, 2017; Tashkandi & Rasheed, 2010; Tokuç et al, 2010; Vakili et al, 2010; Vaseai et al, 2019; Vyas, 2017; Yount & Li, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Of them, 160 full-text articles were assessed for eligibility, and 55 studies were selected to be included in our meta-analysis study (Figure 1) (Abolfotouh & Almuneef, 2019;Afifi et al, 2011;Ahmadi et al, 2017;Akar et al, 2010;Akmatov et al, 2008;Akyazi et al, 2018;Al-Atrushi et al, 2013;Al-Natour et al, 2014;Alper et al, 2005;Alquaiz et al, 2017;Al-Tawil, 2012;S. Asadi et al, 2017, S. Asadi et al, 2019Asian et al, 2019;Barkho et al, 2011;Basar & Demirci, 2018;Diop-Sidibé et al, 2006;Eldoseri et al, 2014;Elnashar et al, 2007;Ergin et al, 2005;Fageeh, 2014;Falb et al, 2019;Faramarzi et al, 2005;Ghahhari et al, 2008;Gibbs et al, 2018;Habib et al, 2011;Haj-Yahia & Clark, 2013;Hajian et al, 2014Hajian et al, , 2018Hamdan-Mansour et al, 2011;Jamali & Javadpour, 2016;Kaplan et al, 2011;Khayat et al, 2017;Mayda & Akkus ¸, 2004;Metheny & Stephenson, 2019;Moghaddam Hosseini et al, 2013;Mohammadbeigi et al, 2019;Mohammadkhani et al, 2009;…”
Section: Information About Selected Studiesmentioning
confidence: 99%
“…Also, the results of studies revealed that psychoeducation intervention such as training of problemsolving skills can reduce the physical and psychological types of committed violence against pregnant women in Iran (28) and China (29). Also, as Hajian et al (30) have reported, a high level of resilience and the use of problem-oriented coping can have a major role in reducing the likelihood of suicide attempt in Iranian females reporting spouse-related abuse (30).…”
Section: Discussionmentioning
confidence: 98%
“…in 2018, reported that stressful life events are associated with suicidal behavior when attempters compared with nonattempters persons. [ 23 ] Previously in variety of studies mentioned to coping skills as important protective factors for stressful life events. [ 24 25 ] In this study, task oriented (efforts aimed at solving the problem) and emotion oriented (emotional reactions) significantly more observed in males.…”
Section: Discussionmentioning
confidence: 99%